Metal-Free Synthesis of α-Aminophosphonates from Tertiary Amines and P(O)H Compounds via a Cross-Dehydrogenative Coupling Reaction - Lin, Binzhou; Lu, Guozhang; Lin, Rongcan; Cui, Yiqun; Liu, Yan; Tang, Guo; Zhao, Yufen (Synlett, 2018)
The various α-aminophosphonates have been prepared from tertiary aromatic and aliphatic amines with P(O)H compounds via a tert-butyl hydroperoxide mediated cross-dehydrogenative coupling reaction, eliminating the need for transition-metal catalysts. The oxidation of tertiary amine by tert-butyl hydroperoxide generates an iminium cation intermediate. A further addition of P(O)H compound to iminium cation gives the desired product.
Keywords: tert-butyl hydroperoxide; α-aminophosphonates; tertiary aromatic amines; tertiary aliphatic amines; dialkyl H-phosphonate